Peningkatan Kreativitas Anak melalui Kegiatan Fun Cooking di Taman Kanak-kanak - Mardian, Nofa; Hartati, Sri (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
Children's creativity ability has not developed due to lack of activities to support children's creativity, so that children's activities are only monotonous with imitation activities. The purpose of this study was to improve the creativity ability of children in the Habibi Pariaman kindergarten. This type of research is classroom action research (CAR). The research subjects for group B early childhood amounted to 12 children consisting of 6 boys and 6 girls. This research was conducted in two cycles, each cycle of which was held three times. The technique used in data collection is observation and documentation, and the results of the assessment are processed by percentage techniques. The results showed that in the first cycle the effect of increasing children's creativity through Fun Cooking activities was 22.5% because it had not yet reached the KKM, the study was continued to cycle II, so that there was an increase in children's creativity through Fun Cooking activities at 82.5% and reaching KKM. Based on these data it can be concluded that Fun Cooking activities can increase creativity of group B children in Habibi Pariaman.